2000
DOI: 10.1054/bjoc.2000.1313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival for cancer in children and young adults in the North of England, 1968–1995: a report from the Northern Region Young Persons’ Malignant Disease Registry

Abstract: The Northern Region Young Persons’ Malignant Disease Registry records information on young people under 25 years old diagnosed with cancer in the Northern Region of England. Incidence and survival rates were calculated for children and young adults diagnosed with cancer between 1968 and 1995. There were 2099 (M:F 1.28:1) children (age 0–14 years) and 2217 (M:F 1.23:1) young adults (15–24 years) diagnosed with a first cancer between 1968 and 1995. The age-standardized rate (ASR) for childhood cancer was 121 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 25 publications
7
110
1
6
Order By: Relevance
“…The rates shown in Table 3 are largely consistent with those found in a small study in this age group in the Northern Region of England and which partially overlaps with the present study (Cotterill et al, 2000). However, the Northern Region study included less than one tenth the number of cases in the present study and variations in rates with respect to diagnostic sub-groups are probably due to the very small numbers resulting in unstable rates for a number of the groups.…”
Section: Discussionsupporting
confidence: 90%
“…The rates shown in Table 3 are largely consistent with those found in a small study in this age group in the Northern Region of England and which partially overlaps with the present study (Cotterill et al, 2000). However, the Northern Region study included less than one tenth the number of cases in the present study and variations in rates with respect to diagnostic sub-groups are probably due to the very small numbers resulting in unstable rates for a number of the groups.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have also shown a general improvement in survival for childhood CNS tumours over the last [20][21][22][23][24][25][26][27][28][29][30] years identifying improvements in CNS embryonal tumour survival specifically (3,16,19,30,31). TYA, aged 16-24 years, from Yorkshire showed a significant increase in survival from medulloblastoma and CNS PNET combined between 1990 and 2009 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system (CNS) tumours are the second most common site of neoplasms diagnosed in children, accounting for approximately one quarter of all childhood cancers (0-14 years), (1) and 14% of tumours diagnosed in teenagers and young adults (TYA) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years) (2). They are the most common cause of cancer related death in children and TYA (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Northern Region Young Person's Malignancy Registry (NRYPMR) collects data at presentation from all patients, aged p25 years diagnosed with a malignant disease in the same geographical area (Cotterill et al, 2000). Patients were included in the present study if they presented between 1 January 1991 and 31 December 2000 with histologically confirmed, newly diagnosed HL, were aged 13 -19 years (inclusive) at diagnosis and were normally resident in the area at the time of diagnosis.…”
Section: Methodsmentioning
confidence: 99%